(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Endocrine ophthalmopathy (EOP) is the most common cause of not only bilateral but unilateral exophthalmos. Differential diagnosis of unilateral exophthalmos demands to exclude other pathologies of orbit and periorbital sinuses. CT and MRI at the present stage are the «gold standard «for the differential diag-nosis of pathological conditions in orbit. Objective. To examine the state of the extraocular muscles in patients with EOC by computer tomography. Material and methods. CT performed in 158 EOP patients using the «Somatom» («Siemens») and spiral computed tomography «Astenion-SUPER-4» firms «Toshiba» by the conventional method. Age of patients ranged from 23 to 77 years, there were 53 men, 105 women. Unilateral exophthalmos diagnosed in 25.9 % of cases, two-sided — in 74.1 %. There were 102 (64.5 %) patients with hyperthyroidism, 35 (22.2 %) with hypothyroidism, 21 (13.3 %) with euthyroid. According to the classification of A. F. Brovkina EOP thyrotoxic exophthalmos installed in 46.2 % of cases, edematous — 43.6 %, endocrine myopathy — 8.8 %. In two patients (1.3 %) with EOP classification group of A. F. Brovkina was not determined. During CT studied the state of extraocular muscles (EOM), optic nerve, retro-bulbar tissue. CT findings were recorded in an electronic database created and processed using the statistical program «Statistics 9.» Results. It was revealed that often affects the internal rectus — 98 patients (62.0 %) and lower — 93 patients (58.9 %), at least the upper — 72 patients ( 45.6 %) and external — 63 patients ( 39.9 %). In hyperthyroidism often marked change in the lower (75.9 %) and internal (65.5 %) rectus of the eye, hypothyroidism — internal (87.5 %), with euthyroid equally eye all muscles increased in 50.0 % of cases. When thyrotoxic and edematous exophthalmos often affected equally all the muscles except the lateral rectus, which is 2 times more increased at thyrotoxic exoph-thalmos. Conclusions. Found that according to CT more frequently (95.6 %) revealed myo- genic form of EOP. The changes of EOM depend on the thyroid function and the clinical form of the thalmopathy EOP.